1987
DOI: 10.1002/app.1987.070340515
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the structure and composition of clinically important polyurethanes by mass spectrometric techniques

Abstract: SynopsisCurie-point pyrolysis maSS spectrometry (Py-MS) and direct probe pyrolysis high resolution mass spectrometry (Py-HRMS) were used to identify the components and additives used in the synthesis and compounding of Biomer, Lycra Spandex, Tecoflex, and Pellethane. Two types of Biomer were identified (P and Q, our notation) which are composed of poly(tetramethy1ene glycol) (PTMG) capped with 4,4'-rnethylenebis(phenylisocya I re) (MDI) and chain-extended with ethylenediamine (EDA). Both forms contain 4,4'-but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1989
1989
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…11,32 Tecoflex is a proprietary aliphatic polyurethane composed of poly (tetramethylene oxide) and dicyclohexyl methane diisocyanate as deduced by mass-spectrometric techniques. 33 Previous studies have shown that Tecoflex is susceptible to in vivo degradation, characterized as environmental stress cracking through the formation of surface fissures resulting from localized hydrolysis of urethane linkages. 34 Degradation has been shown to contribute to mechanical failure of some Tecoflex-based catheter devices.…”
Section: Discussionmentioning
confidence: 99%
“…11,32 Tecoflex is a proprietary aliphatic polyurethane composed of poly (tetramethylene oxide) and dicyclohexyl methane diisocyanate as deduced by mass-spectrometric techniques. 33 Previous studies have shown that Tecoflex is susceptible to in vivo degradation, characterized as environmental stress cracking through the formation of surface fissures resulting from localized hydrolysis of urethane linkages. 34 Degradation has been shown to contribute to mechanical failure of some Tecoflex-based catheter devices.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the presence of three major additives in different BiomerTM lots [7] has been reported. These additives are: a polysiloxane which may be due to 50 contamination during synthesis of polymer [8]; a high-molecular weight UV stabilizer identified as poly(diisopropylaminomethacrylate-co-decylmethacrylate) (PAM) [9]; and an antioxidant, the 4,4'-butylidene bis(6-t-butyl-m-cresol) [10] known under the commercial name Santowhite Powder (SP).…”
mentioning
confidence: 99%